The Superiority of Removable Contact Splints in the Healing of Diabetic Foot during Postoperative Care - Vladimíra Fejfarová; Jaroslav Pavlů; Robert Bém; Veronika Wosková; Michal Dubský; Andrea Němcová; Alexandra Jirkovská; Bedřich Sixta; Karol Sutoris; Filip Thieme; David G. Armstrong; Eliška Vrátná; et al. (Journal of Diabetes Research)
Objective. Off-loading is one of the crucial components of diabetic foot (DF) therapy. However, there remains a paucity of studies on the most suitable off-loading for DF patients under postoperative care. The aim of our study was to evaluate the effect of different protective off-loading devices on healing and postoperative complications in DF patients following limb preservation surgery. Methods. This observational study comprised 127 DF patients. All enrolled patients had undergone foot surgery and were off-loaded empirically as follows: wheelchair+removable contact splint (RCS) (group R: 29.2%), wheelchair only (group W: 48%), and wheelchair+removable prefabricated device (group WP: 22.8%). We compared the primary (e.g., the number of healed patients, healing time, and duration of antibiotic (ATB) therapy) and secondary outcomes (e.g., number of reamputations and number and duration of rehospitalizations) with regard to the operation regions across all study groups. Results. The lowest number of postoperative complications (number of reamputations: p=0.028; rehospitalizations: p=0.0085; and major amputations: p=0.02) was in group R compared to groups W and WP. There was a strong trend toward a higher percentage of healed patients (78.4% vs. 55.7% and 65.5%; p=0.068) over a shorter duration (13.7 vs. 16.5 and 20.3 weeks; p=0.055) in the R group, as well. Furthermore, our subanalysis revealed better primary outcomes in patients operated in the midfoot and better secondary outcomes in patients after forefoot surgery—odds ratios favouring the R group included healing at 2.5 (95% CI, 1.04-6.15; p=0.037), reamputations at 0.32 (95% CI, 0.12-0.84; p=0.018), and rehospitalizations at 0.22 (95% CI, 0.08-0.58; p=0.0013). Conclusions. This observational study suggests that removable contact splint combined with a wheelchair is better than a wheelchair with or without removable off-loading device for accelerating wound healing after surgical procedures; it also minimises overall postoperative complications, reducing the number of reamputations by up to 77% and the number of rehospitalizations by up to 66%.